2019
DOI: 10.3390/ma12244108
|View full text |Cite
|
Sign up to set email alerts
|

Compressive Behaviour of Closed-Cell Aluminium Foam at Different Strain Rates

Abstract: Closed-cell aluminium foams were fabricated and characterised at different strain rates. Quasi-static and high strain rate experimental compression testing was performed using a universal servo-hydraulic testing machine and powder gun. The experimental results show a large influence of strain rate hardening on mechanical properties, which contributes to significant quasi-linear enhancement of energy absorption capabilities at high strain rates. The results of experimental testing were further used for the dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 50 publications
0
18
0
Order By: Relevance
“…The closed cell size test method is already used for the analysis of metallic foams [ 20 , 21 , 22 , 23 ]. The individual closed cell size is presented as D m [ 20 , 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…The closed cell size test method is already used for the analysis of metallic foams [ 20 , 21 , 22 , 23 ]. The individual closed cell size is presented as D m [ 20 , 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…In recent years, metallic foams (MF)s have been used in many engineering fields as lightweight and protective structures due to their high strength properties and outstanding energy absorption capabilities [1][2][3]. Its widespread use in various industries encourages researchers and experts to study the mechanical aspects of these materials [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Closed-cell aluminum solid foam has been widely researched in terms of static and dynamic compression, e.g., [50,51]. Previous works have shown that cellular aluminum with closed cells is sensitive to the strain rate in compression [52,53]. Moreover, article [54] combines a discussion on strain rate sensitivity analysis and energy absorption in closedcell aluminum foams.…”
Section: The Proposition Of New Materials As Earthquake Damage Protectionmentioning
confidence: 99%